PREPARATION AND CHARACTERIZATION OF POLYCRYSTALLINE MIXED NICKEL ZINC FERRITES FOR DIELECTRIC PROPERTIES AND PRACTICAL APPLICATION - VENKATA KUMAR VAGOLU; K. SAMATHA; K. CHANDRA MOULI; J. N. KIRAN; PAUL DOUGLAS SANASI (International Journal of Pharma and Bio Sciences, 2014)
Cobalt substituted Nickel-zinc ferrites of different compositions Ni0.95-xZn0.05CoxFe2O4 and Zn0.95-xNi0.05CoxFe2O4 (where x = 0.00, 0.01, 0.02,0.03, 0.04, 0.05 and 0.06).have been prepared by citrate precursor method involving concerned metals and mixing them in solution state. Parts of the sol-gel powder heated at elevated temperatures were characterized by X-ray diffraction (XRD), Particle size analyser and Scanning Electron Microscope (SEM) to reveal the crystallized single phase structure of the ferrite. Nickel Zinc ferrites are studied for their dielectric and electrical properties upon on the substitution of cobalt. Dielectric constant is found to decreases at lower frequencies and remains constant at higher frequencies, showing the usual dielectric dispersion. The dielectric polarization decrease with increase in frequency and reaches a constant value. The plots of AC conductivity are linear, indicating that the conduction is due to small polarons. A slight decrease in conductivity at certain frequencies is attributed to mixed polaron (small and large) conduction. Room-temperature complex impedance spectra for the samples indicated that size of the semicircle changes with grain size. The dc resistivity (ρdc) increased with the increase of Co2+concentration in NZCF and ZNCF ferrites. The values of activation energy(E) in paramagnetic region is found to be greater than those observed in ferromagnetic region. The ΔE and resistivity are found to increase with increase in cobalt content. The ac resistivity decreased with increase in frequency. In the low frequency region ac resistivity is found increasing with change in composition parameter x. Polycrystalline ferrites (NZCF and ZNCF) are good candidates for Hyperthermia tumour therapy.